The Lithuanian Psychological Well-Being Scale: An analysis of its structure in a student sample - Bagdonas, Albinas; Urbanavičiūtė, Ieva; Kairys, Antanas; Liniauskaitė, Audronė; Girdzijauskienė, Sigita (Psichologija, 2012)
This article presents an analysis of the Lithuanian Psychological Well-Being Scale (LPGS) structure in a student sample and addresses both theoretical and empirical issues related to its development. Psychological well-being is considered to be a broad construct reflecting a subjective evaluation of our lives in certain domains or on the whole. However, theoretical explanations of this phenomenon are somewhat vague and often lack consensus on definitions and classification of well-being domains, subsequently resulting in rather diverse approaches to their empirical evaluation. The rationale for the development of the LPGS is based on the following principles: first, the multidimensionality of the construct (it is assumed that psychological well-being encompasses at least several different domains); second, the necessity to take into account characteristic features of the target population in order to produce a valid Lithuanian instrument; and finally, the empirical investigation approach, i.e. the application of empirical findings for the theoretical explanation of psychological well-being. In total, 461 university students took part in the study (68.8 % female, 31% male, 0.2% non-identified; M = 22.6 years). After conducting exploratory factor analysis and parallel analysis, 91 item was retained and the following subscales were distinguished: Global satisfaction with life and oneself as a person, Negative emotionality, Purposefulness in life, Satisfaction with interpersonal relationships, Satisfaction with family relationships, Satisfaction with the living standards, Satisfaction with physical health, Perceived control, Satisfaction with life in Lithuania. In this study, the LPGS has proven to have adequate psychometric properties. The above-mentioned nine subscales account for 53.7 percent of total variance. The internal consistency test has revealed average to very high subscale reliability, Cronbach alphas ranging from 0.67 (Satisfaction with life in Lithuania) to 0.95 (Global satisfaction with life and oneself as a person).These results provide valuable insight into the dimensionality of psychological well-being in the Lithuanian university student sample. However, more empirical evidence is necessary in order to identify a clear factor structure, and to cross-validate the initial findings in a wider population.
Keywords: psychological well-being; psychological well-being scale